In adenosine A2B knockouts acute treatment with inorganic nitrate improves glucose disposal, oxidative stress, and AMPK signaling in the liver - Peleli, Maria; Hezel, Michael; Zollbrecht, Christa; Persson, A. Erik G.; Lundberg, Jon O.; Weitzberg, Eddie; Fredholm, Bertil B.; Carlstrom, Mattias (Frontiers in Physiology, 2015)
Rationale: Accumulating studies suggest that nitric oxide (NO) deficiency and oxidative stress are central pathological mechanisms in type 2 diabetes. Recent findings demonstrate therapeutic effects by boosting a nitrate-nitrite-NO pathway, an alternative pathway for NO formation. This study aimed at investigating the acute effects of inorganic nitrate on glucose and insulin signaling in adenosine A2B receptor knockout mice (A2B-/-), a genetic model of impaired metabolic regulation. Methods: Acute effects of nitrate treatment were investigated in aged wild-type (WT) and A2B-/- mice. One hour after injection with nitrate or placebo, metabolic regulation was evaluated by glucose and insulin tolerance tests. NADPH oxidase-mediated superoxide production and AMPK phosphorylation were measured in livers obtained from non-treated or glucose-treated mice, with or without prior nitrate injection. Plasma was used to determine insulin resistance (HOMA-IR) and NO signaling. Results: A2B-/- displayed increased body weight, reduced glucose clearance and attenuated overall insulin responses compared with age-matched WT. Nitrate treatment increased circulating levels of nitrate, nitrite and cGMP in A2B-/-, and improved glucose clearance. In WT mice, however, nitrate treatment did not influence glucose clearance. HOMA-IR increased following glucose injection in A2B-/-, but remained at basal levels in mice pretreated with nitrate. NADPH oxidase activity in livers from A2B-/-, but not WT mice, was reduced by nitrate. Livers from A2B-/- displayed reduced AMPK phosphorylation compared with WT mice, and this was increased by nitrate treatment. Injection with the anti-diabetic agent metformin induced similar therapeutic effects in the A2B-/- as observed with nitrate. Conclusion: The A2B-/- mouse is a genetic model of metabolic syndrome. Acute treatment with nitrate improved the metabolic profile, at least partly via reduction in oxidative stress and improved AMPK signaling in the liver.